Pemikiran Ibnu Khaldun Tentang filsafat Pendidikan Islam - Rizki Kurniawan; Riswan Riswan; Sulaeman Abdul Azis; Herdi Herdi; Yurna Yurna (Jurnal Riset Rumpun Agama dan Filsafat, 2023)
Ibn Khaldun's thoughts on the philosophy of Islamic education reflect his valuable contribution in understanding the role of education in the formation and advancement of civilization. In his famous work, "Muqaddimah," Ibn Khaldun expresses a rich and relevant view of education in the Islamic context. Ibn Khaldun considers education as an important element in the formation of individual character and civilization. For him, Islamic education must include moral, ethical, and spiritual dimensions. Ibnu Khaldun argues that early education has a central role in forming the foundation of social life, and emphasizes the importance of providing good education to children from an early age. Apart from early education, Ibn Khaldun also recognized the importance of formal education in forming educated individuals. He recognized the value of knowledge and expertise in community development, and suggested that educational institutions such as madrasas and universities should provide knowledge that is scientific and skill-based. However, Ibn Khaldun also stressed the importance of experiential education in Islamic thought and understanding. He emphasizes that direct experience in social and political interactions brings a deeper understanding of the dynamics of society. According to him, this experience enables individuals to gain wisdom and contextual understanding which is crucial in understanding and applying Islamic teachings in everyday life. In his thoughts, Ibn Khaldun made education a means to achieve social justice and progress of civilization. He recognized the importance of acquiring knowledge and skills, but also emphasized the need for solid moral and spiritual education. For him, Islamic education must combine religious teachings with scientific understanding and practical experience to create individuals who are committed to the good and benefit of humanity.